Pengaruh Belanja Daerah dan Pertumbuhan Ekonomi Daerah Terhadap Kemandirian Keuangan Daerah di Provinsi Jambi - -, Suherman; Herlin, Faradilla; Neldawaty, Rika; Aldi Yanda, Rahmad; Suherman (ILTIZAM Journal of Shariah Economics Research, 2023)
This research is entitled "The Influence of Regional Expenditures and Regional Economic Growth on Regional Financial Independence in Jambi Province. The research aims to measure and analyze: 1). Ratio of regional financial independence, development of regional spending and economic growth in districts/cities in Jambi Province during 2017-2023, 2). The influence of the regional financial independence ratio on regional expenditure in Regencies/Cities in Jambi Province and 3). The influence of the regional financial independence ratio on economic growth in Regencies/Cities in Jambi Province during 2017-2023. Data analysis uses quantitative and quantitative descriptive analysis methods, namely ratio, development and panel data regression. The results of research during 2017-2022 show that on average the districts/cities of Jambi Province have a very low independence ratio, the highest being Jambi City and the lowest being Sungai Full City. All regional expenditures experienced an increase, the highest in Bungo Regency and the lowest in Sungai Banyak City. GRDP all increased, the largest being Sungai Banyak City and East Tanjung Jabung Regency the lowest. The independence ratio has a positive and significant effect on regional expenditure or economic growth of districts/cities in Jambi Province at probability values of 0.0329 and 0.0352.